Designing transition metal and nitrogen-codoped SrTiO3(001) perovskite surfaces as efficient photocatalysts for water splitting. Issue 9 (22nd September 2017) - Yang, Yang; Zheng, Weijie; Cheng, Daojian; Cao, Dapeng
Abstract : Development of an efficient photocatalyst with both strong visible light absorption and high charge mobility is highly desirable but still remains a great challenge. Abstract : Development of an efficient photocatalyst with both strong visible light absorption and high charge mobility is highly desirable but still remains a great challenge. In this work, we use density functional theory (DFT) calculations to investigate the electronic structure and the surface activity of M-doped (M = transition metals V, Cr, Mn, Zr, Nb and Mo) and M–N-codoped (N = nitrogen) SrTiO3 (001) perovskite surfaces in order to obtain the optimal photocatalytic material with both strong visible light absorption and high charge mobility. Results indicate that the N–Nb codoped SrTiO3 (001) surface possesses not only a suitable band gap of 1.90 eV, but also desirable strong visible light absorption and high charge mobility. In addition, by exploring the adsorption and decomposition behavior of water on these modified surfaces, we found that the N–Nb codoped SrTiO3 (001) surface not only has band alignments well positioned for the feasibility of photooxidation and photo-reduction of water, but also significantly reduces the activation energy of the water decomposition reaction. Therefore, the N–Nb codoped SrTiO3 (001) surface designed here is a very promising candidate for water splitting in the visible light region, which provides a theoretical basis for designing new photocatalytic materials.